Assessment of the current spatial-temporal variations of total dissolved solids on the surface waters of Kuala Perlis, Perlis / Aimie Rifhan Hashim ... [et al.] - Hashim, Aimie Rifhan; Kamaruddin, Sharir Aizat; Abd. Aziz, Khairul Naim; Tajam, Jamil; Buyong, Faeiza; Che Ismail, Che-Zulkifli; Lee Abdullah, Anisah; Azis, Tun Mohd Firdaus; Anscelly, Anastacia (UiTM Cawangan Negeri Sembilan, 2023)
Total dissolved solids (TDS) have a terrible impact on river water quality. The issues were compounded further by the health risks posed to residents and the uproar generated by elevated levels of total dissolved solids in the water bodies. This study aims to evaluate the spatial-temporal fluctuations of total solid content, namely total dissolved solids (TDS), on the surface water of Kuala Perlis, Perlis. In December 2021, the sampling sites were established and recorded using Global Positioning Systems (GPS). Five sampling locations were selected for each morning, afternoon, and evening session and water samples were collected and transported into the laboratory. The total dissolved solids were studied using gravimetric analysis and the American Public Health Assessment (APHA) standard. The analysis of variance (ANOVA) was set at 0.05 to determine the significant difference between the spatial-temporal mean readings of TDS using the Statistical Package for the Social Sciences (SPSS) version 26. The TDS ranges were 195.00 mg/L to 4900.00 mg/L, 325.00 mg/L to 9400.00 mg/L, and 296.00 mg/L to 8500.00 mg/L, respectively, for the morning (AM), afternoon (AF), and evening (PM) sampling times throughout five sampling stations. The research found a significant difference in the mean TDS readings concerning spatial variations (p> .05). However, there is no significant difference concerning temporal variations of TDS (p< .05) on the surface waters of Sungai Kuala Perlis. The spatiotemporal findings point to spatial heterogeneity in TDS measurement across sampling station 1, sampling station 2, and sampling station 5 and but not at any different time in Kuala Perlis. The impact of total dissolved solids concentration on living, environment, and riverine infrastructures was also adequately explored. The researcher, the government, and non-governmental organizations can use the preliminary TDS fluctuation data to prepare for the Kuala Perlis region's future social and economic growth by monitoring river health or measuring pollution. The information could also help to improve ecologically friendly river management and protect the Sungai Kuala Perlis ecosystem.